If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 17q + -14xq = 11q Solving 17q + -14qx = 11q Solving for variable 'q'. Move all terms containing q to the left, all other terms to the right. Add '-11q' to each side of the equation. 17q + -11q + -14qx = 11q + -11q Combine like terms: 17q + -11q = 6q 6q + -14qx = 11q + -11q Combine like terms: 11q + -11q = 0 6q + -14qx = 0 Factor out the Greatest Common Factor (GCF), '2q'. 2q(3 + -7x) = 0 Ignore the factor 2.Subproblem 1
Set the factor 'q' equal to zero and attempt to solve: Simplifying q = 0 Solving q = 0 Move all terms containing q to the left, all other terms to the right. Simplifying q = 0Subproblem 2
Set the factor '(3 + -7x)' equal to zero and attempt to solve: Simplifying 3 + -7x = 0 Solving 3 + -7x = 0 Move all terms containing q to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -7x = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -7x = 0 + -3 -7x = 0 + -3 Combine like terms: 0 + -3 = -3 -7x = -3 Add '7x' to each side of the equation. -7x + 7x = -3 + 7x Combine like terms: -7x + 7x = 0 0 = -3 + 7x Simplifying 0 = -3 + 7x The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.Solution
q = {0}
| 3x(t-3)=27 | | x/-11=5 | | F=9/5x+32 | | 9x-(2x-1)=37 | | 36/(2x)=6 | | 5+x=-22 | | 5(7b-6)=110 | | -2(5s-6)-12=-2(9s+4)-3 | | 36/2x=6 | | -1.3+2.7=.2y | | -13x+22=37 | | 7/3a=14 | | y=-9x+44 | | 3x(12-3)=27 | | 6x+19=8x+7 | | -2(5x-6)-12=-2(9s+4)-3 | | b+b2+b/6=190 | | 4*x^3+5*x^2+x=1 | | -10m-4=4-10m | | (4+8x)/(2x+1) | | 180=6000*.12*t | | 4(5x-1)-4=14x-2 | | 5(3x+1)=2(5x-4)+6x | | 27(1.4+1.2)-26(1.4+1.2)= | | -65.375=7.2(9c+1) | | (2x+9)+(2x+8)+(2x)=(2x)+(3x+1) | | 2a/3+1/5 | | 7/3x+9/6x=36/9 | | 10y=12.6 | | -3a+4=-8 | | 6(3x-2)=18x-12 | | 4x^2+19x+22=0 |